The Relationship Between the Online Learning Prosess in Early Chilhood and the Language Development of Pre School - Faizah Suci Damayanti; Zuriati Zuriati; Intan Parulian Tiurma Roosleyn (UM Purwokerto Press, 2021)
Language development is a combination of social interaction, emotional development, intellectual ability, and physical and motor development. However, the development of language in each individual child is different depending on neurological abilities and language development which can affect the stages of language development. Thus, this study aims to determine the implementation of online learning during the Covid-19 case study at TKIT Chiara Depok on the development of preschool language and to find out the inhibiting factors for learning during the Covid-19 period at TKIT Chiara Depok. This study uses descriptive analytic by using a cross sectional design. The population in this study were all parents who have preschool children at TKIT Chiara Depok, with a total of 56 respondents, by performing total sampling, collecting data for the online learning process and language development of preschool children using questionnaires and data processing with coding and analysis. data using the Chi-Square correlation statistical test. The results obtained as many as 78.6% have a good learning process using online methods, while the language development of preschool children is good about 80.4%. There is a moderate positive relationship with p-value = 0.000 (p < 0.05) so that there is a relationship between the online learning process and language development. The conclusion in this study is that there is a relationship between the online learning process and the development of preschool language. With this research, the learning process in the online method that is good in its implementation and preparation will improve the development of good language in preschool children.